Development oF Powtoon-Based Learning Media in SMP Negeri 2 Percut Sei Tuan - Ayu Widiastuti; Cut Latifah Zahari (Study Program of Mathematics Education of Unimed Postgraduate Program, 2022)
PowToon-based learning media is one of the media presented in video format that can be used as an effective learning medium. The purpose of this study was to develop a valid and practical Powtoon-based environmental mathematics lesson based on statistical data for Grade VII students of SMP Negeri 2 Percut Sei Tuan. The subjects of this study were 20 class VII students who were selected using a purposive sampling method. A 4D approach (Define, Design, Development, Dissemination) was used to develop this learning. To demonstrate statistical material in video format, the results of the research are used as learning media for statistical material. The product received a 0.85 score from 3 validators based on very valid criteria. The practicality of the product received a practicality rating of 82.91% with very practical criteria, as evidenced by the results of 20 students' answers regarding the use of a PowToon-based mathematics learning environment on statistics material. In addition, the PowToon-based learning environment is distributed via YouTube for easy access for students. Thus, it can be said that the PowToon-based mathematics learning environment is a valid and practical tool that can be used as a mathematics teaching tool.Keywords: Learning Media, Powtoon, Presenter